2015
DOI: 10.1017/s1743921315006857
|View full text |Cite
|
Sign up to set email alerts
|

Intragroup and Intracluster Light

Abstract: The largest stellar halos in the universe are found in massive galaxy clusters, where interactions and mergers of galaxies, along with the cluster tidal field, all act to strip stars from their host galaxies and feed the diffuse intracluster light (ICL) and extended halos of brightest cluster galaxies (BCGs). Studies of the nearby Virgo Cluster reveal a variety of accretion signatures imprinted in the morphology and stellar populations of its ICL. While simulations suggest the ICL should grow with time, attemp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Krick & Bernstein 2007) have shown that the ICL is more centrally concentrated than the galaxies of the cluster implying that this light is formed via the mergers that build up the BCG. Consequently, there is no clear differentiation between the outskirts of the BCG and the extended ICL (see Mihos 2016). Therefore, we did not attempt to separate both components.…”
Section: Hst Near-ir Data To Characterize the Iclmentioning
confidence: 99%
See 1 more Smart Citation
“…Krick & Bernstein 2007) have shown that the ICL is more centrally concentrated than the galaxies of the cluster implying that this light is formed via the mergers that build up the BCG. Consequently, there is no clear differentiation between the outskirts of the BCG and the extended ICL (see Mihos 2016). Therefore, we did not attempt to separate both components.…”
Section: Hst Near-ir Data To Characterize the Iclmentioning
confidence: 99%
“…In the current cosmological paradigm (ΛCDM), clusters of galaxies are assembled hierarchically by the accretion of galaxies or small galaxy groups. Observationally, one of the most revealing signatures of this assembly is the ICL (see Mihos 2016 for a review). This diffuse light is composed of a substantial fraction of stars, between 5 − 20% of the total amount of stars in the cluster, (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This "missing light" is termed the intrahalo light (IHL) which would permeate the Universe. IHL is to be distinguished from "intracluster light" (ICL; Mihos, 2016;Mihos et al, 2005), associated with clusters of galaxies, which in turn are removed/isolated in CIB fluctuations studies; much of the ICL is further linked to extended halos of brightest cluster galaxies. The mean luminosity of an IHL contributing halo of mass M is assumed to be modeled at rest λ as l λ (M, z) = f IHL (M )[F λ L 2.2µm (M )](1 + z) α with F λ being the SED of the IHL component, normalized to unity at 2.2 µm and assumed to be the same as that of old red stellar populations of elliptical galaxies.…”
Section: E New Diffuse Sources At Intermediate and Low Zmentioning
confidence: 99%
“…Throughout this cluster assembly, individual galaxies interact with one other. During these interactions, matter can be stripped from galaxies and form tidal tails, shells, bridges, and liberating stars from their host galaxies, which contribute to formation of a very faint component of diffuse intacluster light (ICL) (Mihos 2015).…”
Section: Introductionmentioning
confidence: 99%